2011
DOI: 10.1177/1074840711405205
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Family Adaptation in Taiwanese Families Living With Down Syndrome

Abstract: The primary aim of this study was to examine the effects of family demographics, family demands, and family appraisal on adaptation in Taiwanese families of children with Down syndrome. A second aim was to assess the potential mediating effect of family appraisal on the relationship between family demands and adaptation. Eighty-three families completed mailed questionnaires. Data were analyzed using a principal component analysis and a mixed linear modeling. Gender, family demands, and family appraisal were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…Only four studies identified their guiding framework; two used family frameworks, the Resiliency model (Hsiao & Van Riper , Choi & Van Riper ) and Patterson's family resilience model (Choi & Yoo ) and one used an individual‐centric framework, the stress and coping model (Lam & Mackenzie ). Two studies were comparative (Cheng & Tang , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only four studies identified their guiding framework; two used family frameworks, the Resiliency model (Hsiao & Van Riper , Choi & Van Riper ) and Patterson's family resilience model (Choi & Yoo ) and one used an individual‐centric framework, the stress and coping model (Lam & Mackenzie ). Two studies were comparative (Cheng & Tang , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
“…While only one level of adaptation was assessed in most studies, (Cheng & Tang , Choi et al . , Choi & Van Riper , Hsiao ), two levels were assessed in two studies (Hsiao & Van Riper , Choi & Yoo ) and all three levels (individual, dyadic and family) were assessed in two studies (Chiu et al . , Gau et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations